A resource utilization method of secondary aluminum ash and a hydrogen-type two-dimensional sheet layer ZSM-5 molecular sieve prepared by the method and application of the hydrogen-type two-dimensional sheet layer ZSM-5 molecular sieve

CN117049564BActive Publication Date: 2026-10-30GUANGDONG UNIV OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311112786.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-30
Publication Date
2026-10-30
Estimated Expiration
2043-08-30

AI Technical Summary

Technical Problem

[0004]本发明为了解决上述现有技术中二次铝灰堆积或填埋对环境污染及资源浪费的缺陷或不足,提供一种二次铝灰的资源利用方法,采用其作为铝源,调整硅源、二次铝灰和模板剂的用量制得的氢型二维片层ZSM-5分子筛与传统铝源制得的氢型二维片层分子筛的性能相当,不仅实现了废弃物二次铝灰的资源利用,还在获得性能相当的分子筛的同时降低了其制造成本

Benefits of technology

本发明中提供一种二次铝灰的资源利用方法,采用其代替氢型二维片层ZSM-5分子筛中的传统铝源,调整硅源、模板剂与其用量的比例,可以制得与采用传统铝源制得的分子筛性能相当的氢型二维片层ZSM-5分子筛,外比表面积最高可达600 m2/g,介孔孔容达到0.6 m3/g以上。实现了固废的资源化利用,减少了对环境的危害,降低了氢型二维片层ZSM-5分子筛的制造成本。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117049564B_ABST
    Figure CN117049564B_ABST
Patent Text Reader

Abstract

The application discloses a resource utilization method of secondary aluminum ash, a prepared hydrogen type two-dimensional sheet layer ZSM-5 molecular sieve and application. The resource utilization method comprises the following steps: mixing secondary aluminum ash with a silicon source, a template agent, sulfuric acid and water according to a mass ratio of (0.2-1.8):(41-45):(8-20):(3-5):(156-190) to obtain a mixed solution, aging to obtain a gel, crystallizing to obtain a sodium type two-dimensional sheet layer ZSM-5 molecular sieve, then calcining and ion exchanging, and finally calcining to obtain a hydrogen type two-dimensional sheet layer ZSM-5 molecular sieve. The prepared hydrogen type two-dimensional sheet layer ZSM-5 molecular sieve has the same performance as a molecular sieve prepared from a traditional aluminum source, an external specific surface area is up to 600 m 2 / g, a mesopore volume is up to 0.6 m 3 / g or more, and the resource utilization of solid waste is realized, the harm to the environment is reduced, and the manufacturing cost of the hydrogen type two-dimensional sheet layer ZSM-5 molecular sieve is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of molecular sieve synthesis technology, and more specifically, to a method for utilizing secondary aluminum ash resources and the hydrogen-form two-dimensional sheet ZSM-5 molecular sieve prepared therefrom and its applications. Background Technology

[0002] Aluminum ash is a solid waste generated in various stages of alumina electrolysis, processing casting, and aluminum recycling. Secondary aluminum ash is the waste after primary aluminum ash has been used to extract metallic aluminum. Its main components are alumina, aluminum nitride, metallic aluminum, salts, and other components.

[0003] Currently, the existing technologies for handling secondary aluminum ash are as follows: primary aluminum ash can be treated by adding a fluxing agent to recover metallic aluminum, and the process for extracting metallic aluminum from primary aluminum ash is relatively mature; however, the main methods for treating secondary aluminum ash are still landfilling or stockpiling, which can easily cause significant environmental pollution. Therefore, how to utilize waste secondary aluminum ash in a resource-efficient manner has become an urgent problem for enterprises to solve. Summary of the Invention

[0004] To address the environmental pollution and resource waste caused by the accumulation or landfilling of secondary aluminum ash in the prior art, this invention provides a method for the resource utilization of secondary aluminum ash. By using secondary aluminum ash as an aluminum source and adjusting the amounts of silicon source, secondary aluminum ash, and template agent, a hydrogen-form two-dimensional sheet ZSM-5 molecular sieve is prepared, which has performance comparable to that of hydrogen-form two-dimensional sheet molecular sieves prepared with traditional aluminum sources. This method not only realizes the resource utilization of waste secondary aluminum ash but also reduces its manufacturing cost while obtaining a molecular sieve with comparable performance.

[0005] Another object of the present invention is to provide a hydrogen-type two-dimensional sheet ZSM-5 molecular sieve prepared by the above method.

[0006] Another object of the present invention is to provide an application of the above-mentioned hydrogen-type two-dimensional sheet ZSM-5 molecular sieve in alkylation reactions.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for utilizing secondary aluminum ash includes the following steps: S1. Mix silicon source, template agent and water to obtain solution A, then mix solution A with secondary aluminum ash and sulfuric acid to obtain solution B, and age solution B to obtain gel C; S2. Crystallize the gel C described in S1 to obtain sodium-type two-dimensional sheet ZSM-5 molecular sieve; S3. The sodium-type two-dimensional sheet ZSM-5 molecular sieve described in S2 is calcined once to remove the template agent, then ion exchanged in NH4Cl aqueous solution, and calcined a second time to obtain the hydrogen-type two-dimensional sheet ZSM-5 molecular sieve. In step S1, the mass ratio of secondary aluminum ash, silicon source, template agent, sulfuric acid and water in liquid B is (0.2~1.8):(41~45):(8~20):(3~5):(156~190).

[0008] ZSM-5 molecular sieves with a two-dimensional layered structure exhibit high product conversion rates and excellent resistance to deactivation in practical applications, resulting in high catalyst added value. Furthermore, the preparation of two-dimensional layered molecular sieves allows for the creation of hierarchical porous molecular sieves, with the interlaminar spacing (intercrystalline mesopores) providing transport channels and significantly reducing mass transfer resistance. However, the commonly used aluminum sources in the preparation of two-dimensional layered ZSM-5 molecular sieves are aluminum isopropoxide, aluminum sulfate, or sodium aluminate, which are mostly chemical raw materials, leading to high costs. Moreover, the type of aluminum source can influence the layered structure of the molecular sieve, thereby affecting its catalytic performance.

[0009] Normally, secondary aluminum ash, due to its relatively complex composition and low aluminum content, is stockpiled or landfilled. The inventors unexpectedly discovered that using secondary aluminum ash as an aluminum source, combined with appropriate amounts of silicon source and template agent, followed by aging, crystallization, and calcination, yields hydrogen-form two-dimensional sheet ZSM-5 molecular sieves with performance comparable to those obtained from traditional aluminum sources, achieving a maximum external specific surface area of ​​up to 600 m². 2 / g, with a mesoporous pore volume reaching 0.6 m 3 / g or more; when the amount of secondary aluminum ash is too small, the silicon-to-aluminum ratio will be too large, resulting in low activity of the molecular sieve and failure to achieve good catalytic performance; when the amount of secondary aluminum ash is further increased, too much aluminum cannot enter the molecular framework, and the performance of the molecular sieve will not increase further; when the amount of secondary aluminum ash is too large, too much aluminum cannot enter the molecular framework, which may hinder the growth of the molecular sieve and thus affect its catalytic performance.

[0010] It should be noted that those skilled in the art should understand that the secondary aluminum ash is the waste material after the primary aluminum ash has been used to extract metallic aluminum.

[0011] Specifically, the secondary aluminum ash contains 20% to 25% metallic aluminum, 5% to 7% aluminum nitride, and 40% to 50% aluminum element by mass.

[0012] Furthermore, the secondary aluminum ash can be pretreated before being mixed with liquid A. The pretreatment involves mixing the secondary aluminum ash with water, stirring at room temperature for 3-5 days, filtering and washing until neutral, and then drying.

[0013] Furthermore, the template agent is a long-chain amphiphilic bifunctional template agent with the molecular structural formula [C6H]. 13 -N + (CH3)2-C6H 12 -N +(CH3)2-(CH2) 12 -O-(p-C6H4)2-O-(CH2) 12 -N + (CH3)2-C6H 12 -N + (CH3)2-C6H 13 ]·4[Br - ], denoted as C 6-6-12-O Its molecular structure contains four quaternary ammonium salt functional groups, which can interact with [AlO4] through strong electrostatic attraction. - Species interactions lead to the crystallization of the molecular sieve, forming micropores. Long-chain amphiphilic bifunctional templates shorten the length of the b-axis of the ZSM-5 molecular sieve, transforming it from a three-dimensional structure into two-dimensional sheets, thus increasing its external surface area. Long-chain hydrophobic alkyl chains guide the formation of mesopores. The two-dimensional sheet molecular sieves grow interlaced, forming interlayer mesopores, opening the channels of the ZSM-5 molecular sieve, shortening the diffusion path, and reducing diffusion resistance.

[0014] Further, in step S1, the mass ratio of aluminum source, silicon source, template agent, sulfuric acid and water in liquid B is (0.5~1):43:(10~20):(3~4):(165~175).

[0015] Under this raw material ratio, the hydrogen-type two-dimensional sheet ZSM-5 molecular sieve prepared using a four-headed rigid Bola-type surfactant as a template agent has a high external specific surface area and mesopore volume.

[0016] Furthermore, the silicon source mentioned in step S1 is water glass, and the modulus of the water glass is 3.0~3.5 and the Baume degree is 35~45.

[0017] Furthermore, the water glass has a modulus of 3.3 and a Baumé degree of 40.

[0018] Specifically, the sulfuric acid in step S1 has a mass fraction of 98%.

[0019] Furthermore, the aging conditions described in step S2 are conventionally selected in the art, for example, stirring at 50~75°C for 4~8 h.

[0020] In a specific implementation, the aging conditions described above can be stirring at 60 °C for 6 h.

[0021] Furthermore, the crystallization conditions described in step S2 are conventionally selected in the art, for example, crystallization at 140~170℃ and 20 rpm~60 rpm for 5~7 days.

[0022] Specifically, after crystallization in step S2, washing, drying, and calcination are also included. The washing conditions are repeated washing with deionized water until neutral, and the drying conditions are drying at 80~120 ℃ for 8~12 h.

[0023] Furthermore, the conditions for the first and second calcination in step S3 are conventionally selected in the art, for example, calcination in an air atmosphere at 500~600 °C for 4~6 h.

[0024] Furthermore, the ion exchange conditions described in step S3 are conventionally selected in the art, for example, the sodium-type two-dimensional sheet ZSM-5 molecular sieve with the template agent removed can be placed in a 1~2 mol / L NH4Cl aqueous solution for ion exchange.

[0025] In a specific embodiment, the concentration of the above-mentioned NH4Cl aqueous solution can be 1 mol / L.

[0026] Specifically, the above ion exchange conditions are reflux at 80~100 °C for 4~6 h.

[0027] Furthermore, the mass ratio of the sodium-type two-dimensional sheet ZSM-5 molecular sieve with template agent removed to the NH4Cl aqueous solution is 1: (30~50).

[0028] In a specific embodiment, the mass ratio of the sodium-type two-dimensional sheet ZSM-5 molecular sieve with template agent removed to the NH4Cl aqueous solution can be 1:30.

[0029] Unless otherwise specified, all methods described above were performed at room temperature, and those without specified pressure were performed at atmospheric pressure.

[0030] This invention also protects a hydrogen-type two-dimensional sheet ZSM-5 molecular sieve prepared by the above method.

[0031] This invention also protects the application of the above-mentioned hydrogen-type two-dimensional sheet ZSM-5 molecular sieve in alkylation reactions.

[0032] Compared with the prior art, the beneficial effects of the present invention are: This invention provides a method for utilizing secondary aluminum ash, which replaces the traditional aluminum source in hydrogen-form two-dimensional sheet ZSM-5 molecular sieves. By adjusting the ratio of silicon source, template agent, and their amounts, hydrogen-form two-dimensional sheet ZSM-5 molecular sieves with performance comparable to those produced using traditional aluminum sources can be obtained, with a maximum external specific surface area of ​​up to 600 m². 2 / g, with a mesoporous pore volume of 0.6 m 3 / g or more. This achieves the resource utilization of solid waste, reduces environmental harm, and lowers the manufacturing cost of hydrogen-type two-dimensional sheet ZSM-5 molecular sieves. Attached Figure Description

[0033] Figure 1 The image shows the X-ray diffraction pattern of the hydrogen-type two-dimensional sheet ZSM-5 molecular sieve prepared in Example 1 of this invention.

[0034] Figure 2 shows the field emission transmission electron microscope (FET) spectra of the hydrogen-form two-dimensional sheet ZSM-5 molecular sieve prepared in Example 1 of this invention. Figure (a) is magnified at 58,000x and Figure (b) is magnified at 245,000x.

[0035] Figure 3 shows the nitrogen adsorption-desorption isotherms of the hydrogen-type two-dimensional sheet ZSM-5 molecular sieve prepared in Example 1 of the present invention and the commercial ZSM-5 molecular sieve.

[0036] Figure 4 shows the BJH pore size distribution of the hydrogen-type two-dimensional sheet ZSM-5 molecular sieve prepared in Example 1 of the present invention and the commercial ZSM-5 molecular sieve.

[0037] Figure 5 The images show the pyridine infrared spectra of the hydrogen-form two-dimensional sheet ZSM-5 molecular sieve prepared in Examples 1-3 of this invention and the commercial ZSM-5 molecular sieve.

[0038] Figure 6 The infrared spectra of 2,6-di-tert-butylpyridine for hydrogen-form two-dimensional sheet ZSM-5 molecular sieves prepared in Examples 1-3 of this invention and for commercial ZSM-5 molecular sieves are shown.

[0039] Figure 7 The graph shows the toluene conversion rate of the hydrogen-form two-dimensional sheet ZSM-5 molecular sieve prepared in Examples 1-3 of this invention and the commercial ZSM-5 molecular sieve.

[0040] Figure 8 The p-xylene selectivity diagrams are shown for the hydrogen-form two-dimensional sheet ZSM-5 molecular sieves prepared in Examples 1-3 of this invention and commercial ZSM-5 molecular sieves. Detailed Implementation

[0041] To more clearly and completely describe the technical solution of the present invention, the present invention will be further described in detail below through specific embodiments. It should be understood that the specific embodiments described herein are only for explaining the present invention and are not intended to limit the present invention. Various changes can be made within the scope of the claims of the present invention.

[0042] Raw material sources: Secondary aluminum ash was provided by Guangdong Jinyi Alloy Products Co., Ltd., with a mass fraction of 24.65% aluminum, 7% aluminum nitride, and 49.31% aluminum element. Water glass was provided by Shandong Yousuo Chemical Technology Co., Ltd., with a modulus of 3.3 and a Baumé degree of 40. Unless otherwise specified in the examples, conditions were performed according to standard conditions or the manufacturer's recommendations. Reagents or instruments used without a specified manufacturer were all commercially available products. Unless otherwise specified, all reagents used in the examples can be purchased from the market.

[0043] The pretreated secondary aluminum ash is obtained by mixing the above-mentioned secondary aluminum ash with water, stirring at room temperature for 3-5 days, filtering and washing until neutral, and drying.

[0044] Example 1 A hydrogen-form two-dimensional sheet-like ZSM-5 molecular sieve is prepared using a secondary alumina ash resource utilization method, which includes the following steps: S1. Mix 18.4974 g of deionized water and 1.0832 g of C 6-6-12-O Mix and stir until completely dissolved, then add 4.6389 g of water glass to the above solution and stir vigorously until the mixture is homogeneous. Then add 0.108 g of pretreated secondary aluminum ash to the mixture and stir vigorously. Subsequently, add 0.324 g of sulfuric acid and continue stirring. Then age at 60 °C for 6 h to obtain a gel. S2. The above gel was transferred to a reaction vessel and crystallized at 150 °C and 20 rpm for 5 days. After crystallization, the product was filtered and repeatedly washed with deionized water, dried in a drying oven at 100 °C for 12 h, and finally calcined at 550 °C for 5 h to obtain sodium-type two-dimensional sheet ZSM-5 molecular sieve. S3. The obtained sodium-type two-dimensional sheet ZSM-5 molecular sieve was calcined at 550 °C for 5 h to remove the template agent, and then subjected to three ion exchanges in a 1.0 mol / L NH4Cl aqueous solution. The mass ratio of the template-removed sodium-type two-dimensional sheet ZSM-5 molecular sieve to the NH4Cl aqueous solution was 1:30, and the ion exchange conditions were reflux at 80 °C for 6 h. Calcination at 550 °C in air atmosphere for 5 h yielded the hydrogen-type two-dimensional sheet ZSM-5 molecular sieve.

[0045] The mass ratio of the aluminum source, silicon source, template agent, sulfuric acid, and water is 1:43:10:3.4:171.

[0046] Example 2 A hydrogen-type two-dimensional sheet ZSM-5 molecular sieve is provided. The method is basically the same as that in Example 1, except that the mass of pretreated secondary aluminum ash added is 0.054 g, and the mass ratio of aluminum source, silicon source, template agent, sulfuric acid and water is 0.5 : 43 : 10 : 3.4 : 171.

[0047] Example 3 A hydrogen-type two-dimensional sheet ZSM-5 molecular sieve is provided. The method is basically the same as that in Example 1, except that the mass of pretreated secondary aluminum ash added is 0.027 g, and the mass ratio of aluminum source, silicon source, template agent, sulfuric acid and water is 0.25 : 43 : 10 : 3.4 : 171.

[0048] Example 4 A hydrogen-type two-dimensional sheet ZSM-5 molecular sieve is described. The method is basically the same as that in Example 1, except that the amount of silicon source is fixed and the mass ratio of aluminum source, silicon source, template agent, sulfuric acid and water is 0.25: 43:20: 5: 188.

[0049] Example 5 A ZSM-5 molecular sieve was prepared using a method essentially the same as in Example 1, the difference being the addition of C. 6-6-12-O The mass of the sample is 0.324g, and the mass ratio of the aluminum source, silicon source, template agent, sulfuric acid and water is 1.5 : 43 : 10 : 3.4 : 171.

[0050] Comparative Example 1 A ZSM-5 molecular sieve was prepared using a method essentially the same as in Example 1, the difference being the addition of C. 6-6-12-O The mass of the sample is 0.324g, and the mass ratio of the aluminum source, silicon source, template agent, sulfuric acid and water is 0.1 : 43 : 10 : 3.4 : 171.

[0051] Comparative Example 2 A hydrogen-type two-dimensional sheet ZSM-5 molecular sieve is described, and the method is basically the same as in Example 1, except that sodium aluminate is used instead of secondary aluminum ash.

[0052] Result detection The structure of the hydrogen-form two-dimensional sheet ZSM-5 molecular sieve prepared in Example 1 was characterized and analyzed.

[0053] The hydrogen-form two-dimensional sheet-like ZSM-5 molecular sieve prepared in Example 1 was characterized using a Bruker D8 Advance X-ray diffractometer (Germany). The results are as follows: Figure 1 As shown, the sample exhibits characteristic diffraction peaks of ZSM-5 molecular sieve in the wide-angle region of XRD and characteristic diffraction peaks of two-dimensional layered structure in the narrow-angle region of XRD, indicating that the prepared ZSM-5 molecular sieve has an ordered multi-layered two-dimensional layered structure.

[0054] The two-dimensional sheet-like ZSM-5 molecular sieve prepared in Example 1 was characterized using a Talos F200S field emission transmission electron microscope from FEI (Czech Republic). The results are as follows: Figure 2 As shown, the sample exhibits a distinct two-dimensional layered structure with a layer thickness of <10 nm.

[0055] The N2 adsorption-desorption analysis of the two-dimensional sheet-like ZSM-5 molecular sieve prepared in Example 1 was performed using a McMurray ASAP 2460 multi-station fully automated surface area and pore size analyzer under liquid nitrogen conditions (-196 °C). The test results are as follows: Figure 3 and Figure 4 As shown. Figure 3 The BET adsorption isotherms show that the two-dimensional sheet-like ZSM-5 molecular sieve prepared in Example 1 exhibits the characteristics of a Type IV isotherm and a significant desorption hysteresis loop, indicating that the prepared two-dimensional sheet-like ZSM-5 molecular sieve possesses mesoporous material characteristics. Commercial ZSM-5 molecular sieves exhibit Type I adsorption isotherms, typical of microporous materials. From... Figure 4 The BJH pore size distribution shows that the two-dimensional sheet ZSM-5 molecular sieve has obvious mesopores (pore size distribution: 2.5~12 nm), while commercial ZSM-5 molecular sieves do not have mesopore characteristics.

[0056] Elemental analysis of the sheet-like ZSM-5 molecular sieve prepared in the examples was performed using an Agilent ICP-OES instrument (Agilent 5110). The silica-to-alumina ratio was tested, and the results are shown in Table 1. The pore structure parameters of the molecular sieve show that the prepared hydrogen-form two-dimensional sheet-like ZSM-5 molecular sieve possesses both mesoporous and microporous structures. Compared to commercial ZSM-5 molecular sieves, the hydrogen-form two-dimensional sheet-like ZSM-5 molecular sieve prepared in Example 1 has an external specific surface area and mesopore volume that are increased by 6.2 times and 12 times (S⁻¹) respectively. ext 466m 2 / g vs 75 m 2 / g; V meso 0.626 m 3 / g vs 0.052 m 3The addition of secondary alumina ash ( / g) significantly opened up the pore structure of the ZSM-5 molecular sieve, which is beneficial for macromolecular mass transfer and diffusion. Furthermore, ICP-OES elemental analysis showed that the Si / Al ratio of the hydrogen-form two-dimensional sheet ZSM-5 molecular sieve prepared in Example 1 was 33, indicating that secondary alumina ash is suitable as an aluminum source for preparing two-dimensional sheet ZSM-5 molecular sieves, effectively reducing the preparation cost. From Examples 1-3 and Example 5, it can be seen that as the amount of secondary alumina ash increased, the Si / Al ratio of the prepared two-dimensional sheet ZSM-5 molecular sieve gradually decreased to a stable value, while the external specific surface area gradually increased to a stable value, and the mesopore volume gradually increased to a stable value. A larger external specific surface area and mesopore volume indicate that the two-dimensional sheet ZSM-5 molecular sieve has more exposed external surface, better openness, and facilitates mass transfer, thus improving performance stability and catalytic performance. Comparison of the examples, comparative examples, and commercially available molecular sieves shows that a decrease in micropore specific surface area and a reduction in micropores contribute to mass transfer and increased catalytic activity.

[0057] Table 1 Performance parameters of molecular sieves in the examples and comparative examples

[0058] Pyridine and 2,6-di-tert-butylpyridine were used as probe molecules to collect data on the molecular sieve catalysts prepared in Examples 1-3 using a Bruker Vertex 70 Fourier transform infrared spectrometer (BIR). The concentrations of Brønsted acid and Lewis acid were calculated using Beer's law. The results are as follows: Figure 5 , Figure 6 As shown in Table 2.

[0059] from Figure 5 As can be seen, in the pyridine-IR spectra of the two-dimensional sheet ZSM-5 molecular sieves with different silica-to-alumina ratios, all the two-dimensional sheet ZSM-5 molecular sieves exhibited characteristic absorption peaks of the Brønsted acid sites at ~1545 cm⁻¹. -1 The characteristic absorption peak is attributed to the adsorption of pyridine molecules at the Brønsted acid site, at ~1455 cm⁻¹. -1 The characteristic absorption peak is attributed to the adsorption of pyridine molecules at Lewis acid sites.

[0060] from Figure 6 As can be seen, in the 2,6-di-tert-butylpyridine-IR spectra of the two-dimensional sheet ZSM-5 molecular sieves with different silica-to-alumina ratios, the Brønsted acidic sites of the present invention are all located at ~1616 cm⁻¹. -1 The characteristic absorption peaks at the Brønsted acid sites on the outer surface of ZSM-5 molecular sieves are mainly due to the large molecular size of 2,6-di-tert-butylpyridine (kinetic diameter 0.79 nm), which allows it to adsorb only onto ZSM-5. The molecules can adhere to the outer surface of the molecular sieve, rather than being adsorbed into the pores of the ZSM-5 molecular sieve (0.53 nm × 0.56 nm; 0.51 nm × 0.55 nm).

[0061] Table 2 Acid concentrations of molecular sieves in Examples 1-3

[0062] As can be seen from Table 2, from Example 1 to Example 3, as the aluminum content decreases, the concentrations of total Brønsted acid and outer surface Brønsted acid of the two-dimensional sheet ZSM-5 molecular sieve prepared using aluminum ash continuously decrease, and the number of active sites gradually decreases, indicating that the catalytic activity of the two-dimensional sheet ZSM-5 molecular sieve gradually decreases.

[0063] The catalysts prepared in Examples 1-3 were granulated and passed through a 20-30 mesh sieve. Approximately 0.2 g of the sample was mixed with 1.0 g of quartz sand for catalytic performance evaluation. Activation was performed at 450°C for 2 h in a N2 atmosphere. A reaction solution was prepared by mixing toluene and methanol at a molar ratio of 1:1, and the flow rate was adjusted to a mass hourly space velocity (HHSV) of 39 h⁻¹. -1 At 400℃ and atmospheric pressure, catalyst deactivation is considered to occur when the conversion rate falls below 50% of the maximum value. The test results for toluene conversion and para-xylene selectivity in Examples 1-3 are as follows: Figure 7 and Figure 8 As shown.

[0064] from Figure 7 and Figure 8It can be seen that the hydrogen-form two-dimensional sheet ZSM-5 molecular sieve prepared by the present invention using aluminum ash has a good catalytic effect on the alkylation reaction of toluene and methanol. Example 1 showed the highest toluene conversion rate of 55% and the longest service life. Although the Brønsted acid concentration of Examples 1-3 (0.040-0.067 mmol / g) was much lower than that of commercial ZSM-5 (0.122 mmol / g), their conversion rate and service life were higher than those of commercial ZSM-5 molecular sieves. This is mainly attributed to the fact that the molecular sieves of Examples 1-3 have a two-dimensional sheet structure, a short mass transfer path, and more accessible acid sites (Brønsted acid on the outer surface accounts for half of the total Brønsted acid). In contrast, commercial ZSM-5 molecular sieves have a traditional microporous structure and almost no Brønsted acid on the outer surface, which is the reason for their rapid deactivation. The molecular sieve prepared in Example 1 has comparable performance to that prepared in Example 5. The hydrogen-form two-dimensional sheet ZSM-5 molecular sieve in Example 4 has comparable performance to that in Example 2. The two-dimensional sheet ZSM-5 molecular sieve prepared using secondary aluminum ash provided by this invention has a shorter diffusion path, more accessible acid sites, and better catalytic performance, which is of great significance for the recycling and resource utilization of secondary aluminum ash.

[0065] In Comparative Example 1, the insufficient amount of aluminum source resulted in an excessively high silicon-to-aluminum ratio, leading to low activity of the prepared molecular sieve and an inability to achieve good catalysis.

[0066] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art should understand that other variations or modifications can be made based on the above description, and it is neither necessary nor possible to exhaustively describe all possible implementations here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.

Claims

1. The application of hydrogen-form two-dimensional sheet-like ZSM-5 molecular sieve in the alkylation reaction of methanol and toluene, characterized in that, The hydrogen-form two-dimensional sheet ZSM-5 molecular sieve is prepared using a secondary aluminum ash resource utilization method, including the following steps: S1. Mix silicon source, template agent and water to obtain solution A, then mix solution A with secondary aluminum ash and sulfuric acid to obtain solution B, and age solution B to obtain gel C; The template agent is a four-ended rigid Bola-type surfactant [C6H] 13 -N + (CH3)2-C6H 12 -N + (CH3)2-(CH2) 12 -O-(p-C6H4)2-O-(CH2) 12 -N + (CH3)2-C6H 12 -N + (CH3)2-C6H 13 ]·4[Br - ]; S2. Crystallize the gel C described in S1 to obtain sodium-type two-dimensional sheet ZSM-5 molecular sieve; the crystallization conditions are 140~170 ℃ and 20 rpm~60 rpm for 5~7 days; S3. The sodium-type two-dimensional sheet ZSM-5 molecular sieve described in S2 is calcined once to remove the template agent, then ion exchanged in NH4Cl aqueous solution, and calcined a second time to obtain the hydrogen-type two-dimensional sheet ZSM-5 molecular sieve. In step S1, the mass ratio of secondary aluminum ash, silicon source, template agent, sulfuric acid and water in liquid B is (0.5~1):43:(10~20):(3~4):(165~175); the silicon source in step S1 is water glass; the modulus of the water glass is 3.3 and the Baume degree is 40.

2. The application according to claim 1, characterized in that, The secondary aluminum ash contains 20% to 25% metallic aluminum, 5% to 7% aluminum nitride, and 40% to 50% aluminum element by mass.

3. The application according to claim 1, characterized in that, The conditions for both the first and second calcination in step S3 are calcination in an air atmosphere at 500~600 ℃ for 4~6 h.

4. The application according to claim 1, characterized in that, The ion exchange conditions described in step S3 are as follows: the sodium-type two-dimensional sheet ZSM-5 molecular sieve with the template agent removed is placed in a 1~2 mol / L NH4Cl aqueous solution for ion exchange.

5. The application according to claim 1, characterized in that, The mass ratio of sodium-type two-dimensional sheet ZSM-5 molecular sieve with template agent removed to NH4Cl aqueous solution is 1:(30~50).

Citation Information

Patent Citations

  • Method for preparing fluid catalytic cracking (FCC) gasoline small-molecule sulfur densification catalyst

    CN102895991A

  • Preparation method of MFI micro-mesoporous lamellar molecular sieve with different interlayer spacings

    CN103449466A

  • Hydrogen-type ZSM-5-at-Beta composite molecular sieve catalyst and preparation method and application thereof

    CN114160192A

  • Method for using aluminum ash as fuel, correction material and sintering aid for dry cement production

    CN114524630A

  • Aluminum ash resource utilization method

    CN116586408A